The $800 million pill : the truth behind the cost of new drugs - Goozner, Merrill, 1950- (University of California Press, 2004)
"Drug companies insist that [prescription drug] prices reflect the millions they invest in research and development ... Merrill Goozner contends that American taxpayers are in fact footing the bill twice: once by supporting government-funded research and again by paying high prices for prescription drugs. Goozner demonstrates that almost all of the important and life-saving new drugs of the past quarter-century actually originated from research at taxpayer-funded universities and the National Institutes of Health ... [Goozner] suggests ways that the government's role in testing new medicines could be expanded to eliminate private-sector waste driving up the cost of existing drugs--p. [2] of jacket